Attitudes toward sentencing guidelines and simulated sentencing among Missouri circuit court judges - Aruguete, Mara S. (American journal of criminal justice, 2004)
This study examines attitudes toward sentencing guidelines and simulated sentencing practices among Missouri circuit court judges. In addition, the study investigates the efficacy of sentencing workshops by comparing judges who attended or did not attend workshops. All Missouri circuit court judges were mailed surveys and 97 judges responded. Results indicated that judges generally felt positive toward Missouri’s voluntary sentencing guidelines, but often failed to refer to the guidelines when sentencing sample cases. Attendance at a sentencing workshop was not associated with attitudes about Missouri sentencing guidelines or sentencing in simulated cases. Sentencing in simulated cases varied by nature of the crime and circuit type. Judges from metropolitan areas tended to sentence more leniently than judges from rural areas. In their written comments, many judges expressed fear about the possibility of mandatory guidelines. Results suggest that there is ambivalence among Missouri judges over the acceptance and use of sentencing guidelines.